Mainstreaming Open Textbooks: Educator Perspectives on the Impact of OpenStax College open textbooks - Rebecca Pitt (Athabasca University Press, 2015)
This paper presents the results of collaborative research between OpenStax College, who have published 16 open textbooks to date, and the OER Research Hub, a Hewlett funded open research project examining the impact of open educational resources (OER) on learning and teaching.  The paper focuses primarily on the results of two surveys that were conducted with educators during 2013 and 2014/2015. These surveys focused on use and perceptions of OER and OpenStax College materials, financial savings and perceptions of impact on both educators and students.  This paper reports on the research findings related to the impact of OER on educator practice and make a series of specific recommendations based on these findings.